2014
DOI: 10.1155/2014/105405
|View full text |Cite
|
Sign up to set email alerts
|

Water Physicochemistry and Zooplankton Fauna of Aiba Reservoir Headwater Streams, Iwo, Nigeria

Abstract: The physicochemical water condition and zooplankton fauna of the two main inflows of Aiba Reservoir were assessed over an annual hydrological cycle (May 2013-March 2014. The concentrations of total solids (TS) and total suspended solids (TSS) in the two streams were unusually higher in the dry season for typical inland waters of Nigeria and showed a decrease from the upper reaches towards the lower reaches (reservoir's inlet). Dissolved oxygen, NO 3 − , and PO 4 3− recorded their highest concentrations at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…The NO 3 values observed in the present study were low compared to results of some studies in Nigerian rivers (Igbinosa et al, 2012;Yusuf et al, 2017;Amah-Jerry et al, 2017;Anyanwu and Emeka, 2019). However, NO 3 values recorded during this study were within or little below the results of Anyanwu and Ukaegbu (2019) and Kindele and Olutona (2014), both obtained in Nigeria.…”
Section: Physical-chemical Parameterssupporting
confidence: 59%
“…The NO 3 values observed in the present study were low compared to results of some studies in Nigerian rivers (Igbinosa et al, 2012;Yusuf et al, 2017;Amah-Jerry et al, 2017;Anyanwu and Emeka, 2019). However, NO 3 values recorded during this study were within or little below the results of Anyanwu and Ukaegbu (2019) and Kindele and Olutona (2014), both obtained in Nigeria.…”
Section: Physical-chemical Parameterssupporting
confidence: 59%
“…Small streams may carry clear water for most parts of the year whereas, during the rainy season, the water may carry a moderate amount of dirt, organic debris, and suspended materials [ 5 ]. As streams move close to inhabited or dumpsite areas, water quality can undergo various forms and levels of deterioration capable of eroding the availability of water for humans and ecosystems and even decrease species diversity within a given ecosystem [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Station 2 (2.975) had value that is higher than Ajuonu et al (2011) But lower than Abdul et al (2016) attributable to the effect observed in Shannon-Weiner indices. Akindele and Olutona (2014) also recorded Margalef indices values of between 1 and 3; which also attributed to environmental pollution and instability. Margalef index has no upper limit but most of the diversity indices give high values to stable communities and low values to unstable ones; thereby revealing environment variability attributed to environmental degradation (Mason 2002;Yeom and Kim, 2011;Shah and Pandit, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…This observation could be attributed to the effect of anthropogenic activities exacerbated by season. Akindele and Olutona (2014) recorded Shannon-Weiner indices values of <3.0, which was attributed to polluted and unstable environment. Bonny Estuary is the home to the Nigeria Liquified Natural Gas Project, which could seriously impact on the environment.…”
Section: Discussionmentioning
confidence: 99%